2018
DOI: 10.1177/0024363918770462
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Contraception Use on the Reproductive Health of Adolescents and Young Adults

Abstract: Oral contraceptives (OCs) are often prescribed to adolescents and young adults for the treatment of health problems and to avoid unwanted pregnancies. We hypothesized that the use of OCs, among adolescents and young adults, is associated with a greater likelihood of pregnancy, abortion, sexually transmitted diseases (STDs), pelvic inflammatory disease (PID), and sexual behaviors that will enhance those problems (i.e., earlier sexual debut and more sexual partners) than adolescents and young adults not using OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Demographic variables included birth year, marital status, race, ethnicity, and religious affiliation, as these variables may impact contraceptive use. [22][23][24] Military characteristics included Service branch, receipt of combat exposure pay (as a proxy for exposure for combat), and MST screening results (positive or negative). While MST status was not routinely screened for or reliably captured in structured data until 2004, Veterans who accessed care prior to 2004 were screened at follow-up encounters and those responses analyzed.…”
Section: Measures and Analysesmentioning
confidence: 99%
“…Demographic variables included birth year, marital status, race, ethnicity, and religious affiliation, as these variables may impact contraceptive use. [22][23][24] Military characteristics included Service branch, receipt of combat exposure pay (as a proxy for exposure for combat), and MST screening results (positive or negative). While MST status was not routinely screened for or reliably captured in structured data until 2004, Veterans who accessed care prior to 2004 were screened at follow-up encounters and those responses analyzed.…”
Section: Measures and Analysesmentioning
confidence: 99%
“…Being raised in an intact household has been shown to be associated with greater contraceptive use as an adult (Fehring et al, 2018; Hayford & Guzzo, 2013). It has been demonstrated that having an intact family, especially having both biological parents, results in a dynamic of open communication, which includes sex communication between parents and children (Hicks et al, 2013; Manlove et al, 2014; Osuchowski-Sanchez, 2011; Sevilla et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Yet, without making a direct religious objection to the pill and other contraceptives, it can be seen that these behaviors that might be termed sinful can be directly linked to the use of contraception in our culture. Fehring, Bouchard, and Meyers (2018) showed additional correlations between contraceptive use in adolescents and negative sexual outcomes. There are additional arguments that can be made against it, including the deleterious effects of cohabitation on the subsequent marriage and divorce rate, the contamination of the water supply by hormonal drugs, and declining fertility rates.…”
Section: Final Remarksmentioning
confidence: 96%